Cost-effective analysis of automated programming optimization in cardiac resynchronization therapy: Holistic Markov modelling. Issue 6 (June 2022) - Noda, Takashi; Lu, Xiaoxiao; Ishiguro, Yoko; Ikuemonisan, Joshua; Holbrook, Reece; Tsintzos, Stelios; Kusano, Kengo
Highlights: Up to one third of patients do not derive clinical benefit despite improvements in cardiac resynchronization therapy (CRT). An algorithm allowing automated optimization of pacing for CRT (AdaptivCRT) has been introduced. Positive clinical impact including mortality and heart failure hospitalization of AdaptivCRT was observed. New technology is usually provided at a higher purchase price than the conventional system. The use of AdaptivCRT was projected to avoid costs under a Japanese healthcare delivery setting. Abstract: Background: Automated optimization algorithm (AdaptivCRT; Medtronic, Mounds View, MN, USA) allowing automated optimization of cardiac resynchronization therapy (CRT), has been introduced. However, little is known concerning its cost-effectiveness. This study aims to evaluate the potential economic benefits of AdaptivCRT of CRT. Methods: Markov modelling was informed by empirical data sourced from the AdaptivCRT Clinical Trial. Published meta-analyses were used to derive the impact of increasing response to hospitalization and mortality risks. Response was assessed via the clinical composite score. Results: Deterministic results suggested a mean survival of 10.97 years with adaptive algorithms against 10.5 years without (+0.47 in favour of novel algorithms). Heart failure hospitalization costs were modelled to ¥1, 382, 753 (US 12, 686) with novel devices against ¥1, 524, 747 (US 13, 989) with previous technology models. Sensitivity analyses show CRT with Adaptive algorithm was projected to provide cost savings in all scenarios. Conclusions: The use of AdaptivCRT was projected to improve average patient survival and avoid costs in a Japanese healthcare setting. Graphical abstract: Image, graphical abstract .